Cash usage in Poland in 2020: Insights into the role of the COVID-19 pandemic and spatial aspects - Radosław Kotkowski; Arkadiusz Manikowski (Journal of Banking and Financial Economics (JBFE), 2023)
The study explores the factors likely to induce Polish customers to pay by cash, instead of payment cards, for goods and services they are purchasing. The basis of our investigation is microdata obtained in 2020, during the "Payment Habits in Poland in 2020" study, which was conducted by Narodowy Bank Polski (National Bank of Poland) in 2020. The analysis is performed using the two-stage Heckman approach. In the first stage, card adoption factors are analyzed using a probit model; then, in the second stage, the OLS model is employed to analyze the propensity to pay by cash, despite having a payment card. Apart from typical factors affecting the use of different payment methods, e.g., age, income, education, or perceptions about payment methods, we find an important role of two, yet under-investigated factors, namely: the COVID-19 pandemic and spatial aspects. E.g., we find that self-reported change in payment behavior during the pandemic indeed was reflected in diary studies. Furthermore, we show that instances of merchants' refusal to accept cash significantly impacted payment choices. Moreover, the results indicate significant spatial heterogeneity in payment behavior and that aspects like distance to the nearest ATM impacted cash usage, as more cash is used when ATMs are farther away, illustrating the concept of "cash burns." Lastly, it has been noticed that during the pandemic, ownership of contactless payment cards significantly reduced cash usage, most probably due to the fear of contracting the disease by physical contact with surfaces (like cash).
Keywords: E41; D12; L81; 330; cash; payment cards; payment behavior; customer payment choice; Heckman approach